STRATEGI PENGEMBANGAN ASPEK KOGNITIF KELOMPOK B ANAK USIA DINI PADA PEMBELAJARAN JARAK JAUH - Indri indri Ristiani; Lily Yuntina (UNIVERSITAS PGRI MADIUN, 2022)
AbstractThe purpose of this study was to find out and obtain information about the strategy for developing cognitive aspects of early childhood in distance learning through playing while learning activities using smart tree learning media in an effort to recognize initial numbers. The object of group B students at TKIT Mafaaza Bekasi City, consisting of 8 male students and 12 female students. The qualitative descriptive research approach and the type of classroom action research with the Kemmis Taggart model, consisting of 2 cycles, each cycle has 4 stages, namely observation, planning, implementation and observation/reflection. The concept of distance learning with virtual zoom with a child - centered learning strategy where the teacher is a facilitator and motivator . Data collection techniques are interviews, observations and documentation. The results showed that the development of cognitive aspects with learning activities while playing using smart trees in the early observation / pre-cycle 42% category began to develop. After the first cycle reached 57% the category of children developed as expected and after the second cycle the average development of cognitive aspects was 81% the cognitive category developed very well.Keywords: Early Childhood Cognitive Development Aspects, distance learning strategies. AbstrakTujuan penelitian ini untuk mengetahui dan mendapatkan informasi tentang Strategi Perkembangan aspek kognitif anak usia dini pada pembelajaran jarak jauh melalui kegiatan bermain sambil belajar menggunakan media pembelajaran pohon pintar dalam upaya pengenalan angka permulaan . Objek pada siswa kelompok B di TKIT Mafaaza Kota Bekasi, terdiri 8 siswa laki-laki dan 12 siswa perempuan Pendekatan penelitian deskriptif kualitatif dan Jenis penelitian tindakan kelas dengan model Kemmis Taggart, terdiri dari 2 siklus setiap siklus ada 4 tahapan yaitu observasi, perencanaan, pelaksanaan dan pengamatan/ refleksi. Konsep pembelajaran jarak jauh dengan virtual zoom dengan strategi pembelajaran berpusat pada anak dimana guru sebagai fasilitator dan motivator . Teknik pengumpulan data wawancara, observasi dan dokumentasi. Hasil penelitian menunjukan bahwa perkembangan aspek kognitif dengan kegiatan belajar sambil bermain dengan menggunakan pohon pintar pada observasi awal / pra siklus 42% kategori mulai berkembang. Setelah dilakukan siklus I mencapai 57% kategori anak berkembang sesuai harapan dan Setelah dilakukan siklus II rata-rata perkembangan aspek kognitif sebesar 81% kategori kognitif berkembang sangat baik.Kata kunci: Aspek Perkembangan Kognitif anak usia dini , Strategi pembelajaran jarak jauh .